Urban air pollution and emergency department visits for injury in Edmonton and Toronto, Canada - Mieczysław Szyszkowicz; Errol M. Thomson; Nicholas de Angelis; Curtis Lavoie; Thắng Chiến Nguyễn (Elsevier, 2022)
Air pollution is associated with a broad spectrum of health conditions. Among the reported associations are central nervous system effects, suggesting that air pollution may also affect human behavior and reaction time, which could in turn increase likelihood of injury. Injuries impose a significant public health and economic toll, but to our knowledge the relationship with air pollution has not been examined. This study investigated associations between air pollution and emergency department (ED) visits for injury and poisoning in two Canadian cities (Edmonton, Toronto). Daily concentrations of carbon monoxide, ozone, sulfur dioxide, nitrogen dioxide, and fine particulate matter (PM2.5), and two air quality indexes (AQHI, AQHIX; incorporating O3, NO2, and PM2.5), were considered. A time-stratified case-crossover design and conditional Poisson regression models were used to study short-term exposure effects (0 to 14 day lags). The analysis was done by sex, age group, and season. Significant positive associations were observed in both cities, albeit with some differences in the pattern of effects across strata. Relative risks (RR) and 95% confidence intervals (CI) for an interquartile range (IQR) increase of NO2 (IQR=13.0 ppb, Edmonton) in cold season (October-March) for male were RR=1.012 (95% CI: 1.005, 1.018), 1.025 (1.018, 1.031), 1.026 (1.020, 1.033), and 1.025 (1.019, 1.032), for lags from 0 to 3 days, respectively. The corresponding results in Toronto (IQR=8.8 ppb) were: 1.010 (1.004, 1.017), 1.007 (1.000, 1.013), 1.009 (1.003, 1.016), and 1.007 (1.000, 1.013). The data suggest a potential association between air pollution and increased number of ED visits for injury.